Verification of Material Composition and Manufacturing Process of Carbon Fibre Wheel - Manas, Lukas; Rusnakova, Sona; Javorik, Jakub; Zaludek, Milan; Fojtl, Ladislav (Manufacturing Technology Journal, 2019)
Presented research paper is focused on the development of carbon fibre wheel. Considering development and construction of wheels for the automotive and motorcycle industry, low weight is one of the most significant factors. In the case of rotating components, the imbalance of the assembly is a problem. This fact affects handling of the vehicle or wheel behavior under the load, for example in the point of turning, acceleration or drive on damaged road. Determination of the most appropriate material composition (sequence) is primarily the main problem of composite material application. Correct design of material composition and also lay-up diagram is determined by material characteristics and strength requirements. A suitable solution is in the application of a group of input material structures creating hybrid composite. Specific combination of various input materials (aluminum ring, 3D printed plastic honeycomb core and carbon fibre composites) guarantees and ensures the fulfilment of the strength requirements which are determined during each particular application. The main aim of presented paper was to design material composition and shape of carbon fibre wheel that were subsequently verified by successful manufacturing process.
Keywords: Composite Material; Carbon Fibre; Hybrid Core; Prepreg; Wheel